2017
DOI: 10.15698/mic2017.12.603
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial energy metabolism is required for lifespan extension by the spastic paraplegia-associated protein spartin

Abstract: Hereditary spastic paraplegias, a group of neurodegenerative disorders, can be caused by loss-of-function mutations in the protein spartin. However, the physiological role of spartin remains largely elusive. Here we show that heterologous expression of human or Drosophila spartin extends chronological lifespan of yeast, reducing age-associated ROS production, apoptosis, and necrosis. We demonstrate that spartin localizes to the proximity of mitochondria and physically interacts with proteins related to mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Nonetheless, so far very few SPART loss-of-function mutations have been reported (3, 4, 6, 47-51) (Supplemental Table S2). Animal (null mice) and cellular models (Spartin silencing/overexpression) showed a role for Spartin in different processes, including neuronal survival/sprouting, cell division, and mitochondrial stability (7,8,10,12,13,19).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nonetheless, so far very few SPART loss-of-function mutations have been reported (3, 4, 6, 47-51) (Supplemental Table S2). Animal (null mice) and cellular models (Spartin silencing/overexpression) showed a role for Spartin in different processes, including neuronal survival/sprouting, cell division, and mitochondrial stability (7,8,10,12,13,19).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these cells also showed metabolic changes with severe decrease in complex I (NADH dehydrogenase) activity, increased production of mitochondrial reactive oxygen species (ROS) and elevated extracellular pyruvate, which reflects defective mitochondrial oxidation of this molecule. Interestingly, in a recent study, heterologous expression of human or Drosophila Spartin extended yeast lifespan, reduced age-associated ROS production and cell death (19). Spartin localized to the proximity of mitochondria, physically interacting with proteins related to mitochondrial and respiratory metabolism in yeast (19).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…reported that a decrease of spartin could promote an increase in neuronal axons, and the long‐term deficiency of intracellular spartin could lead to neuronal growth damage and mitochondrial distortion . Mitochondrial energy metabolism is closely related to spartin's function . Joshi and Bakowska found that the plant‐related senescence domain of spartin interacts with cardiolipin in mitochondria.…”
Section: Discussionmentioning
confidence: 99%